2018
DOI: 10.1097/mop.0000000000000572
|View full text |Cite
|
Sign up to set email alerts
|

New developments in immunotherapy for pediatric leukemia

Abstract: The use of immunotherapy for leukemia has been successful in creating durable remissions for multiply relapsed and refractory patients who previously had little chance of cure. The ongoing clinical and preclinical work continues to advance our understanding of these immune-based therapies, and will shape the next generation of clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 46 publications
0
24
0
Order By: Relevance
“…Given recent reports of relapses after initially successful blinatumomab or CAR T-cell therapy for ALL, perhaps an immunesupportive role for metformin is worth exploring in leukemia or other cancers. [31][32][33] Metformin is of increasing interest in cancer prevention and under study in active therapeutic trials for various malignancies including lung, colon, pancreatic, prostate, head and neck, gynecological, and breast cancers. 34 The established safety, probable antileukemic effect and possible immune-supportive effects of metformin, warrant additional investigation and may provide a future role for metformin in the treatment of ALL.…”
Section: Discussionmentioning
confidence: 99%
“…Given recent reports of relapses after initially successful blinatumomab or CAR T-cell therapy for ALL, perhaps an immunesupportive role for metformin is worth exploring in leukemia or other cancers. [31][32][33] Metformin is of increasing interest in cancer prevention and under study in active therapeutic trials for various malignancies including lung, colon, pancreatic, prostate, head and neck, gynecological, and breast cancers. 34 The established safety, probable antileukemic effect and possible immune-supportive effects of metformin, warrant additional investigation and may provide a future role for metformin in the treatment of ALL.…”
Section: Discussionmentioning
confidence: 99%
“…Other exciting developments in the field of immunotherapy include bispecific T‐cell engagers (BiTE), which are molecules containing two antibodies that will result in binding of both the CD3 domain of T cells and a surface antigen on the malignant cell. When bound to both targets simultaneously, the BiTE will signal the T cell to degranulate, resulting in damage to the malignant cell . A pediatric phase I/II trial demonstrated a complete remission rate of 39% after two cycles of BiTE therapy .…”
Section: Discussionmentioning
confidence: 99%
“…IV therapeutics such as blinatumomab and other CD19-directed immunotherapies [ 34 , 35 ] can trigger the rapid release of inflammatory mediators and cellular cytokines into the blood. Organ toxicity affecting cardiovascular, respiratory, neurologic, and renal function may result.…”
Section: Safety Profile Of Blinatumomabmentioning
confidence: 99%
“…One proposed mechanism for neurotoxicity is the release of neurotoxic cytokines and chemokines by blinatumomab-activated T cells en route to the central nervous system, causing inflammation at the neuroendothelium [ 36 ]. Neurotoxicity is also seen with the administration of other CD19 immunotherapies [ 34 , 35 ]. For example, axicabtagene ciloleucel and tisagenlecleucel are two CD19 chimeric antigen receptor T-cell agents that have boxed warnings for neurologic toxicities (e.g., encephalopathy, delirium, or seizures) in their FDA-approved labels [ 37 , 38 ].…”
Section: Safety Profile Of Blinatumomabmentioning
confidence: 99%